ChemInform Abstract: Combining Solid‐State NMR Spectroscopy with First‐Principles Calculations — A Guide to NMR Crystallography. Issue 29 (29th June 2016) - Ashbrook, Sharon E.; McKay, David
Abstract: Review: 144 refs.